Les Retombées Psychologiques du Covid-19 "Anxiété et Déprime" - Boucherit, Saci (جامعة عنابة, 2022)
جائحة كورونا لا تميز بشكل عام بين الجنسية أو العرق أو الجنس أو العمر. إن الأزمة الحالية تزعزع استقرار كما البالغين والشباب على حد سواء لأنها تجعلهم يشعرون بعدم الاستقرار. إنه يهدد التوازنات الهشة، ويزيد من عدم الاستقرار، وقبل كل شيء يسبب القلق أو حتى الاكتئاب، ويغير أنماط المعاملات بين الأفراد. إنها تهدد التوازنات الهشة، وتزيد من عدم الاستقرار، وقبل كل شيء تسبب القلق أو حتى الاكتئاب، وتغير أنماط المعاملات بين الأفراد. بذلك سوف نركز على التأثيرات المتعلقة بالقلق والاكتئاب على سكان العالم من خلال تحديد بعض التوصيات العلاجية. The Covid-19 pandemic does not generally make any distinction based on nationality, ethnicity, gender or age. The current crisis upsets and destabilizes both adults and young people when it does not cause them to mourn. It threatens fragile balances, amplifies precariousness, above all causes anxiety or even depression, modifies transactional patterns between individuals. Let us focus on the impacts relating to anxiety and depression in the world population by pinning down some therapeutic recommendations.
Keywords: الصحة النفسية -- الاضطرابات النفسية -- الرعاية النفسية -- جائحة كورونا "كوفيد-19"